Reading Comprehension through Jigsaw Technique - M. Sabiqul Huda (JURNAL ILMIAH EDUKATIF, 2019)
Reading skill is too dominant in the English language exam. Nearly 75 percent of questions contained in the test are reading comprehension. Therefore, teachers are required to focus more on reading skills without neglecting the other skills. However, in Sambas sub district senior high school; some of the students face difficulties to comprehend the text. It is because the students lack in vocabulary. Besides that, they are not interested because of the monotonous teaching technique. So, the writer offers Jigsaw technique to handle the problems. This paper examines concept of reading, reading strategies, concept of jigsaw and the previous research in reading comprehension through Jigsaw.